EFEKTIVITAS PENGGUNAAN APLIKASI GOOGLE MEET SEBAGAI MEDIA PEMBELAJARAN ONLINE PADA MAHASISWA SAAT PANDEMI COVID-19 - Meilla Dwi Nurmala; Tubagus Umar Syarif Hadi Wibowo; Tubagus Farihal Fatah (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
Covid-19 is a virus that was first discovered in the city of Wuhan, China at the end of 2019. Its rapid transmission made the WHO declare the Covid-19 outbreak a global pandemic. This prompted the Minister of Education, Culture, Research and Technology of the Republic of Indonesia, Nadiem Anwar Makarim, to issue circular letter number 4 of 2020 concerning the Implementation of Education in the Coronavirus Disease (Covid-19) Emergency Period. Learning must be carried out online. Online learning is learning that is carried out virtually in their respective homes. The application that is often used by lecturers and students in carrying out online learning is Google Meet. The purpose of this study is to find out how effective online learning is using Google Meet. The research method used is descriptive quantitative with a non-test instrument, namely interviews. The results obtained are that online learning using the Google Meet application has been effective in delivering material during the Covid-19 pandemic. Using the Google Meet application as an online learning medium has various advantages, namely a) it is easier to use, b) does not suck up a lot of internet quota, c) does not require a signal that is always stable, sometimes in up-and-down signal conditions can still follow learning, and d) the available features are easy to understand how to use